Inside the penal voluntary sector: Divided discourses of “helping” criminalized women - Quinn, Kaitlyn (Punishment & society, 2020)
Neoliberal austerity measures and welfare state retrenchment have meant that voluntary organizations around the globe are increasingly called upon to perform statutory social services. Despite a large and rising presence in criminal justice service delivery, volunteers and voluntary organizations have scarcely received scholarly analysis. This paper uses interviews, ethnography, and document analysis to explore the penal voluntary sector in Canada. Specifically, how individuals in the penal voluntary sector understand their roles in helping criminalized women and how these perspectives vary across different positions. This paper illuminates how agents occupying different helper positions cultivate divergent understandings of (and justifications for) the help they provide. Bourdieu’s field theory is mobilized to demonstrate how variegated discourses of helping co-exist, conflict, and impact the relational dynamics of the penal voluntary sector and its engagement with criminalized women.